Coordination compounds of 4, 5, 6, 7-tetrahydro-1H-indazole with Cu(II), Co(II) and Ag(I): structural, antimicrobial, antioxidant and enzyme inhibition studies. Issue 24 (17th December 2017) - Khan, Ezzat; Gul, Zarif; Shahzad, Adnan; Jan, Muhammad Saeed; Ullah, Farhat; Tahir, M. N.; Noor, Awal
Abstract: Coordination behavior of 4, 5, 6, 7-tetrahydro-1 H -indazole (H-Ind) with Cu(II), Co(II), and Ag(I) was studied. The ligand affords complexes bearing different geometries depending upon the metal and anion present in the starting salts. Five compounds with different structural perspectives, trans -[CuCl2 (H-Ind)4 ] (1 ), trans -[CuBr2 (H-Ind)4 ] (2 ), trans -[Cu(CH3 COO)2 (H-Ind)2 ] (3 ), trans -[CoCl2 (H-Ind)4 ] (4 ), and [Ag(H-Ind)2 ]NO3 (5 ), were obtained. The ligand adopts tetrahydro-1 H -indazole isomeric form in Cu(II) and Co(II) complexes and with Ag(I) ion the same ligand adopts tetrahydro-2 H -indazole form. In the case of sterically demanding acetate counter ion in contrast to Cl or Br, the Cu(II) ion accepts two equivalents of the ligand and four-coordinated square planar complex was obtained. With AgNO3, the expected complex was obtained. The yield of reactions was >80% and all complexes were obtained as crystalline material from the reaction mixtures. Their structures were determined by X-ray diffraction and all complexes were tested for antibacterial ( Enterobacter sakazkii, Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniea ), antifungal ( Aspergillus flavus, Aspergillus fumegatus, Aspergillus nigar, Fusarium oxysporium ), and antioxidant (2, 2′-azino- bis (3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH)) activities. The same were also tested as inhibitors against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) . Abstract :